Michael Jackson video greatest hits history - Jackson, Michael, 1958-2009 (New York : Epic Music Video, 2001)
A compilation of music videos performed by Michael Jackson
Brace yourself -- A kaleidoscope of Michael Jackson history -- Billie Jean -- The way you make me feel -- Black or white -- Rock with you -- Bad -- Thriller -- Beat it -- Remember the time -- Don't stop'til you get enough -- Heal the world
Title from title screen
Features: optional on-screen lyrics, discography
DVD format
Keywords: Popular music -- 1981-1990; Popular music -- 1991-2000; Popular music -- 1971-1980